ANALISIS BENDING PADA KOMPOSIT SERAT ALAM DAUN AGEL DENGAN RESIN EPOXY - Sahuburua, Stevward Norenssio; Hartini, Dwi; Adiputra, Bangga Dirgantara (Vortex, 2023)
The use of composite materials, especially those developed by natural fibers in various equipment, has begun to develop a lot, the use of natural agel leaf fibers as composite materials can reduce the use of synthetic materials and increase the utilization of agel leaf natural fibers which are still a lot of wasted. This study aims to determine the stages or processes of agel leaf natural fiber composite using 2 methods of hand lay up, vacuum bag and to determine the value of the bending strength of agel leaf natural fiber material between variations of the epoxy matrix in the direction of the fibers 0^°  and 〖90〗^°.Based on the data from the test results, it can be concluded that the average value of maximum bending strength in agel leaf natural fiber composites using the vacuum bag manufacturing method with a volume fraction of 60% and fiber direction 0^°  and 〖90〗^° has an average maximum bending strength value that is the highest, namely 11.006 MPa and 11.057 MPa and the composite of agel leaf natural fiber using the hand lay up method (non vacuum bag) with a volume fraction of 50%, 60%, 70% and fiber direction 0^° has the lowest average maximum bending strength values of 3.413 MPa, 5.404 MPa, 4.625 MPa.